Characterising Residual Stresses in a Dissimilar Metal Electron Beam Welded Plate. (2015) - Venkata, K. Abburi; Truman, C.E.; Smith, D.J.
Abstract: Dissimilar metal welded components are becoming increasingly common in industrial applications especially in the nuclear sector. Dissimilar metal welding refers to the joining of two materials from different alloy groups. One of the basic requirements of the dissimilar metal welded joint is that the joint strength should be greater than or equal to that of the weakest member and a careful characterisation of the joint is crucial before considering the applicability of the dissimilar metal welded components. The current paper explores the feasibility of an electron beam welded joint between ferritic/martensitic Grade 91 or more commonly known as modified P91 and austenitic 316LN stainless steel, without the addition of any filler material. The residual stress distribution arising from the welding is determined from measurements using neutron diffraction experiment and predictions using finite element analysis. The measured data has been analysed using Rietveld and single peak fits. The finite element analysis was conducted on a two-dimensional cross-sectional model using ABAQUS code, implementing the effects of solid-state phase transformation experienced by P91 steel. The predicted residual stresses are compared with the experimental measurements and conclusions are drawn on the final residual stress distribution.